Oxidative stress in vascular surgical diseases: mechanisms, impacts and therapeutic perspectives - Xu, Haosen; Yang, Jin; Wei, Zhanhui; Bao, Shijie; Liu, Zhuo (Frontiers in Pharmacology, 2025)
The role of oxidative stress in vascular surgical diseases has increasingly been recognized as significant. This paper systematically reviews the specific mechanisms of oxidative stress in a various vascular surgical condition, including aortic dissection, abdominal aortic aneurysm, thrombosis, diabetic foot, and thromboangiitis obliterans, while also exploring related therapeutic strategies. Oxidative stress arises from an imbalance between free radicals and antioxidants, where excess reactive oxygen species and other free radicals can exacerbate inflammatory response. This paper delves into the pathogenic mechanisms of oxidative stress in the aforementioned diseases and discusses potential methods for utilizing antioxidants to reduce oxidative stress levels. Additionally, this paper highlights the challenges faced by current antioxidant therapies and identifies future research directions. By summarizing current research progress, this paper aims to provide a theoretical basis for more effective treatment strategies of vascular surgical diseases, with the hope of advancing the field.